Neurotrophin-4 and Brain-Derived Neurotrophic Factor Serum Levels in Renal Transplant Recipients with Chronic Pruritus - Kinga Tyczyńska; Piotr K. Krajewski; Danuta Nowicka-Suszko; Dariusz Janczak; Hanna Augustyniak-Bartosik; Magdalena Krajewska; Jacek C. Szepietowski (Adis, Springer Healthcare, 2023)
Abstract Introduction Chronic pruritus (CP) is a common symptom defined as a sensation that provokes the desire to scratch and which lasts for at least 6 weeks. CP remains a problem for up to 21.3% of renal transplant recipients (RTRs). Our research aimed to establish the possible association between serum levels of neurotrophin-4 (NT-4) and brain-derived neurotrophic factor (BDNF) and the presence and intensity of CP in RTR. Methods The study was performed on a group of 129 RTRs, who were divided according to the presence or absence of pruritus in the previous 3 days. The assessment of pruritus was performed with the use of a numeric rating scale (NRS), 4-Item Itch Questionnaire (4IIQ), and Itchy Quality of Life (Itchy QoL). A total of 129 blood samples with a volume of 9 ml were drawn from RTRs during the monthly routine control. Serum levels (pg/mL) of NT-4 and BDNF were measured by the ELISA. Results Pruritic RTRs have statistically significantly higher serum concentrations of NT-4 serum level compared to non-pruritic RTRs (229.17 ± 143.86 pg/mL and 153.08 ± 78.19 pg/mL [p = 0.024], respectively). Moreover, a statistically significant difference between pruritic and non-pruritic RTRs with healthy controls was shown (p < 0.001 and p < 0.001, respectively). Although there was a numerically higher serum concentration of BDNF in pruritic RTRs (32.18 ± 7.31 pg/mL vs. 31.58 ± 10.84 pg/mL), the difference did not reach statistical significance. No statistically significant difference was also seen in BDNF serum levels between RTRs and healthy controls. Furthermore, there was a statistically significant, positive correlation between serum concentration of NT-4 and NRS score (p = 0.008, r = 0.357). Conclusions The results indicate higher NT-4 serum concentration in RTRs with pruritus compared to RTRs without pruritus. Furthermore, the study revealed a statistically significant, positive correlation between the serum concentration of NT-4 and NRS score.